EXISTENCE OF A CURRENT PRICE AS A PRECONDITION FOR ABSTRACT METHOD FOR CALCULATING DAMAGES IN INTERNATIONAL AND SERBIAN SALES LAW - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
If the contract is avoided and there is a current price for the goods, the party claiming damages may recover the difference between the price fixed by the contract and the current price at specific time and at specific place. Abstract calculation of loss is possible only when the contract goods have current price. Current price is the price generally charged for such goods sold under comparable circumstances in the trade concerned. According to the CISG and Serbian Law of Obligations, for the determination of the current price is relevant time of avoidance. This general rule is not applicable in international sales law when the party claiming damages has avoided the contract after taking over the goods. In that case, the current price at the time of taking over shall be applicable instead of the current price at the time of avoidance. Current price rule contained in the Art. 76(2) of the CISG presupposes that the current price is the price prevailing at the place where the delivery of the goods should have been made, or if there is no current price at the place, the price at such other place as serves as a reasonable substitute, making due allowance for differences in the cost of transporting the goods. Pursuant to Art. 524(2) Of Serbian Law of Obligations, however, relevant is the price in the market of the place of effecting the transaction. Formulation place of effecting the transaction is unclear and vague and can create different problems. Therefore, this rule should be amended and the relevant place should be the place of delivery.